Analytical solution of the associative mean spherical approximation for the ion-dipole model - Holovko, M.F.; Kapko, V. (Condensed Matter Physics, 1998)
A simple electrolyte in a polar solvent is modelled by a mixture of polar hard
spheres and equal diameter charged hard spheres with the possibility of
ionic dimerization. The analytical solution of the associative mean spherical
approximation (AMSA) for this model is derived to its full extent. Explicit
expressions for pair correlation functions and dielectric constant in terms
of the AMSA are established. Some numerical calculations illustrate the
role of ionic association. Простий електроліт моделюється в полярному розчиннику сумішшю
полярних твердих сфер і однакового розміру заряджених твердих
сфер із можливою іонною димеризацією. Подано аналітичний розв’язок асоціативного середньо-сферичного наближення для цієї моделі
(АССН). Приводяться точні вирази для парних кореляційних функцій і
діелектричної константи в термінах АССН. Роль іонної асоціативності
ілюструється числовими результатами.